On-line Transient Stability Assessment using Matlab parallel programming environment - Soykan, Gürkan; Dağ, Hasan (IEEE, 2009)
Transient Stability Assessment (TSA) is the major part of Dynamic Security Assessment (DSA) in an electric power system. On-line TSA has gained more importance for power system security in last two decades. The decreasing costs of hardware and advanced package programs and techniques encourage researchers to apply parallel programming to the problems that are either too much time consuming or impossible to solve using serial computers. The real-time evaluation of TSA is now almost possible thanks to such tools and techniques. We demonstrate the use of the parallel computing toolbox of Matlab for TSA. In this regard, IEEE 57 and 118 bus systems are tested with 57 and 56 contingencies respectively. Each contingency requires solution of a transient stability problem. The parallel performance of this implementation is expected to spur researchers to use parallel programming in Matlab environment. It requires minimal knowledge regarding parallel programming.
Keywords: N/A